Efeito do exerc??cio vibrat??rio e cicloergom??trico sobre diferentes sistemas corporais em jovens sedent??rias - Silva, Rog??rio Wagner da (2016)
For some time it has become common to use the whole body vibration training (IVC) for its benefits in a short period of time per session. This study evaluated the changes introduced in the body composition, bone mineral density, in hematological variables and the interleukins IL2, IL4, IL6, IL10, IFN-?? and TNF-??; resulting from training sessions and detraining after physical exercise in vibrating platform and a stationary bike. The final sample of 26 young sedentary women after divided into two groups: Vibration Group (GV) age 20.77 ?? 2.86 years and body mass index (BMI) 22.72 ?? 3.67 and Ergometry Group (GE) aged 20.62 ?? 4.35 years and body mass index (BMI) 21.31 ?? 4.18, both performed two distinct training programs, with 06 weeks of exercises and 06 weeks of detraining. Assessment and reassessment was carried out in three stages (T1, T2 and T3) predetermined to evaluate the changes in parameters that could be the result of conducted training. After compilation and analysis of data, significant changes in body composition were observed in bone mineral density, even in white blood count series. Significant response (p <0.050) in the collection times were identified in both groups for the variables: Hemoglobin and MCH; also we observed strong tendency to MCHC. Were also detected changes to IL2 was identified significant alteration being T1 and T2 (P <0.011) and between T1- T3 (P <0.003). While IFN-?? the major change came only between T1 and T2 (P <0.003). The results for IL-4, IL-6, IL-10 and TNF-?? has been found that these cytokines have different responses according to the type of physical activity undertaken between groups (GV x EG) and also over time (T1, T2 and T3). These results lead us to conclude that there is physiological adaptation to training and detraining independent of the type of exercise performed.